2021
DOI: 10.1123/ijspp.2020-0620
|View full text |Cite
|
Sign up to set email alerts
|

Additional Clothing Increases Heat Load in Elite Female Rugby Sevens Players

Abstract: Purpose: To determine whether elite female rugby sevens players are exposed to core temperatures (Tc) during training in the heat that replicate the temperate match demands previously reported and to investigate whether additional clothing worn during a hot training session meaningfully increases the heat load experienced. Methods: A randomized parallel-group study design was employed, with all players completing the same approximately 70-minute training session (27.5°C–34.8°C wet bulb globe temperature) and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
(44 reference statements)
0
6
1
Order By: Relevance
“…These identified barriers require practice-facing solutions, such as the use of additional/thermal clothing and/or post-exercise thermal exposures [e.g. hot water immersion (HWI)] [22][23][24] . Indeed, a recent study showed that additional/thermal clothing, with or without post-exercise-HWI, were both shown to procure comparable performance improvements to those obtained from a 'classical' 10 day laboratory HA block in well-trained athletes 24 .…”
Section: Heat Acclimation/acclimatizationmentioning
confidence: 99%
See 1 more Smart Citation
“…These identified barriers require practice-facing solutions, such as the use of additional/thermal clothing and/or post-exercise thermal exposures [e.g. hot water immersion (HWI)] [22][23][24] . Indeed, a recent study showed that additional/thermal clothing, with or without post-exercise-HWI, were both shown to procure comparable performance improvements to those obtained from a 'classical' 10 day laboratory HA block in well-trained athletes 24 .…”
Section: Heat Acclimation/acclimatizationmentioning
confidence: 99%
“…Perhaps reflective of these barriers and certainly indicative of technological advancement, ingestible telemetric temperature pills were commonly considered within the practice of practitioners in this study. Indeed, their use within elite sporting competition sees growth year on year 14,17,22,27,28 .…”
Section: Ehi/ehs Experiencementioning
confidence: 99%
“…Notably, some of these instances of T c ≥ 39.0°C occurred during warm‐ups, while four individuals reached a T c of > 39.0°C on more than one occasion. Previous investigations have demonstrated that playing minutes have a significant effect on individual post‐game T c during international rugby sevens tournaments in both male (Taylor et al, 2019) and female (Henderson et al, 2020b) athletes, even in modest environmental conditions. This relationship is also present in the current study ( p < 0.0001, η 2 p = 0.29), with game time being > 6 min on 16/17 occasions when post‐game T c was > 39.0°C.…”
Section: Discussionmentioning
confidence: 99%
“…There has been limited investigations into how HA would best fit into an elite rugby sevens environment due to the competing influences of other training demands, travel and tournaments (Casadio, Kilding, Cotter, & Laursen, 2017). With traditional HA recommendations being largely unfeasible in an elite rugby sevens setting, practical solutions, such as wearing additional clothing during training have been shown to provide an increased thermal stimulus, without impacting external running load during training sessions (Henderson et al, 2020b). In turn, utilising common pre-and per-cooling strategies such as the ingestion of ice slushy (Beaven et al, 2018;Brade, Dawson, & Wallman, 2014), application of icetowels (Duffield, Steinbacher, & Fairchild, 2009;Minett, Duffield, Marino, & Portus, 2012) and ice vests pre and during warm up (Taylor et al, 2019) has been suggested as best practice in team sports (Aldous et al, 2018;Tyler, Sunderland, & Cheung, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…18 The e-Celsius TM system has also been used previously within elite rugby sevens matches 14,16 and training. 19,20 In the case of technological error or the capsule being passed prior to data collection [this occurred for 6 of the 38 attempted measures (19 participants x 2 measures each)], resting Tc data were not able to be collected. Cardiovascular fitness changes were indirectly monitored by tracking changes in HRex to a 4minute submaximal continuous run at 12 km•h -1 and recording the final 30 seconds mean value.…”
Section: Participantsmentioning
confidence: 99%